Clinical Patterns and Demographic Characteristics of Dermatophytosis in Surabaya - Azzahra, Safira; Ervianti, Evy; Setiabudi, Rebekah (Institute of Topical Disease Universitas Airlangga, 2024)
Dermatophytosis, the most common fungal infection in humans, significantly impacts quality of life due to its clinical and cosmetic effects. Its high prevalence underscores the need to evaluate patient profiles to improve management strategies. This study aim is to identify the most prevalent type of dermatophytosis, patient demographics, clinical characteristics, laboratory investigations, and therapy in dermatophytosis into the clinical and epidemiological characteristics of dermatophytosis in a tropical, high-burden region. This descriptive retrospective study used total sampling of medical records of dermatophytosis patients from January 2017 to December 2022. Tinea corporis and tinea cruris was the most common, while tinea manuum is the least common dermatophytosis. Female adults were the most affected group. Common clinical features for each type included alopecia for tinea capitis, erythematous macules for other types, and nail dystrophy for tinea unguium. Trichophyton mentagrophytes was the commonest pathogen in 2017. Most of the therapies followed Clinical Practice Guidelines with extensive use of griseofulvin and ketoconazole cream. Further research should explore therapeutic outcomes, preventive measures, and factors influencing recurrence and adherence to treatment.